Solvent optimization and characterization of fatty acid profile and antimicrobial and antioxidant activities of Turkish Pistacia terebinthus L. extracts - Durak, Muhammed Zeki; Ucak, Gulsum (Tubitak Scientific & Technological Research Council Turkey, 2015)
The present study investigated 12 different Pistacia terebinthus L. (terebinth) fruits, harvested or purchased in Turkey, for fatty acid composition, radical scavenging, antimicrobial activity, and total phenolic content. Solvent optimization for the samples was prepared by using a simplex lattice mixture design prior to the analysis. The optimum solvent mixture was 39% water and 61% acetone, based on the maximization of extraction yield of phenolic compounds. Total phenolic contents (TPCs) of the extracts varied from 12,189 mg GAE/1000 g extract to 36,392 mg GAE/1000 g extract. 2,2-Diphenyl-1-picrylhydrazyl (DPPH) radical scavenging activities of the extracts varied over a wide range (8.86%-64.43%) and were highly correlated with TPCs. Agar diffusion was used to determine the antibacterial activity of the terebinth extracts against 2 gram-positive (Staphylococcus aureus and Listeria monocytogenes) and 2 gram-negative (Escherichia coli O157: H7 and Salmonella enterica subsp. enterica serovar Typhimurium) bacteria. L. monocytogenes and Salmonella Typhimurium were more susceptible to the extracts than E. coli O157: H7 and S. aureus. Considering the fatty acid composition of the extracts, palmitic acid, oleic acid, and linoleic acid were the dominant saturated, monounsaturated, and polyunsaturated fatty acids, respectively. In conclusion, this study confirmed the terebinth fruits' strong bioactive and antimicrobial properties and established their fatty acid profiles, indicating their potential for a variety of applications.
Keywords: Antimicrobial; antiradical; fatty acid; mixture design; phenolic; Pistacia terebinthus L.; BIOACTIVE COMPOUNDS; ESSENTIAL OILS; OLIVE OILS; FRUIT; SEED; TEMPERATURE; PHENOLICS; RESPONSES; CAPACITY; STEROLS; Agriculture; Forestry